Evaluation of ELISA kits for the screening of four nitrofuran metabolites in aquaculture products according to the European guideline for the validation of screening methods. Issue 2 (1st February 2021) - Gaudin, Valérie; Hédou, Céline; Rault, Annie; Verdon, Eric; Soumet, Christophe
ABSTRACT: The administration of nitrofurans to livestock to treat or prevent animal diseases has been banned in the EU for the production of food of animal origin. The corresponding marker residues are tissue-related metabolites AMOZ, AHD, SEM, and AOZ. The MRPL (minimum required performance limit)/RPA (Reference point for action) was set at 1 µg kg −1 in the EU. Thus, all the laboratories involved in the control of nitrofuran metabolites must detect at least at this analytical limit of performance. The objectives of the work reported here were to evaluate the performance of ELISA kits from two different manufacturers (R-Biopharm, Germany; Europroxima, the Netherlands) for the individual screening of the four nitrofuran metabolites (AOZ, AMOZ; AHD; and SEM) in aquaculture products (fish, shrimps), and then to validate the kits according to the European Decision EC/2002/657 and to the European guideline for the validation of screening methods. The false positive rates were below 9 % for the kits from both manufacturers. The detection capabilities CCβ determined were all below the current RPA (1 µg/kg). However, regarding the updated RPA at 0.5 µg/kg that shall apply in 2022, the AMOZ and SEM kits from R-Biopharm and the SEM kit from Europroxima will not be able to reach it.